2000
DOI: 10.1007/s10582-000-0058-1
|View full text |Cite
|
Sign up to set email alerts
|

Laser spectroscopy of fission fragments

Abstract: The study of the nuclear structure of fission fragments is discussed. They are neutronrich nuclei the structure of which posses some peculiarities. Two regions of fission fragments are discussed: near the shell closures N=50 and N=82 and at the boundary of the deformation. A view on the optical properties of these elements is presented and different laser spectroscopic methods for their investigation are proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2003
2003

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Among the general trends of such investigations are measurements of nuclear multipole moments and ~-and V-spectra of the fission fragments. The measurements of the nuclear moments and changes of the nuclear mean squared radii by laser spectroscopic methods have been already discussed in our previous work [8]. The information obtained can be substantially extended and improved by measurements of f~-and v-ray anisotropy of polarized nuclei.…”
Section: A242mentioning
confidence: 89%
See 1 more Smart Citation
“…Among the general trends of such investigations are measurements of nuclear multipole moments and ~-and V-spectra of the fission fragments. The measurements of the nuclear moments and changes of the nuclear mean squared radii by laser spectroscopic methods have been already discussed in our previous work [8]. The information obtained can be substantially extended and improved by measurements of f~-and v-ray anisotropy of polarized nuclei.…”
Section: A242mentioning
confidence: 89%
“…are suitable for resonance optical excitation. An analysis of the optical properties of the atoms and multicharged ions of fission fragments in question showed that this condition is fulfilled for most fission fragments [8]. Therefore, the laser radiation could be effectively used for fission fragment polarization and experiments with polarized fragments could play a role as a new source of information about nuclides far off ~-stability.…”
Section: Implantation Of Beams Of Polarized Atoms In a Crystalmentioning
confidence: 99%
“…In order to calibrate these factors for the transition studied, the stable Ce isotopes were also measured on the 331 nm line in this work and combined with atomic measurements on the pure s → p transition at 446 nm to form a King plot [9]. The mass factor of the pure transition can be estimated to be M 446 = +479(332) GHz [10], and the field factor has been calculated to be F 446 = −6031(305) MHz fm −2 [11][12][13]. The gradient and intercept of the King plot allow these factors to be deduced for the 331 nm transition, giving M 331 = −666(504) GHz and F 331 = +2031(103) MHz fm −2 .…”
Section: Discussionmentioning
confidence: 99%
“…We observe that Eu is a special case, where the BW-effect as well as the hfa is known. In addition, there have been done measurements of the hfs in a long chain of isotopes [11][12][13], making it possible to use the method of Persson [7] to extract the hfa.…”
Section: Hyperfine Anomaly In the Lanthanidesmentioning
confidence: 99%
“…The studied states, the ionic ground state 9 S 4 and the metastable 7 S 3 , are dominated by the contact interaction in such a way that the ratio A s A À Á differs very little between the states leading to an large uncertianty, as discussed earlier, making them unuseful for this purpose. Neither is it meaningful to try and use them with the other results [11][12][13] as the hfa is deduced using the known hfs for the stable Eu isotopes as a calibration, nor is an analysis of the hfs in the states involved possible.…”
Section: Hyperfine Anomaly In the Lanthanidesmentioning
confidence: 99%